Anar Chemicals and adulteration of auto fuels - Guha, Apratim, (SAGE business cases, 2021)
Anar Chemicals Pvt. Ltd., an Ahmedabad-based small chemical manufacturing company, bids for a tender floated by the Indian Oil Corporation Ltd. The tender is for detecting adulteration of motor fuels by kerosene sold at a subsidized price through the Indian public distribution system. The Indian Oil Corporation Ltd. offers to detect the adulteration by collecting samples from gas stations across India and testing the samples for the presence of a marker premixed with the kerosene distributed though the public distribution system. The case introduces the concept of group testing, and requires the student to utilize that concept to determine how Anar Chemicals Pvt. Ltd. can control the cost of testing.